Tratamento de efluente da produção de trifluralina por oxidação-coagulação com ferrato de potássio e processos fenton combinados - Wilde, Marcelo Luís (2006)
The so called amination water (AW), an effluent stream from the industrial production of the trifluraline herbicide, toxic and recalcitrant to conventional treatments such as the microbiological, was submitted to a combined advanced process. For the degradation study of this effluent a recent, promising alternative was chosen - the potassium ferrate (K2FeO4) oxidation-coagulation - that demonstrates high oxidant capability (from 2.2 up to 0.72 V) in a large pH range. In this study, a response surface methodology (RSM) design using pH and K2FeO4 concentration as independent variables, and the absorptiometric color reduction as a dependent one, was applied. The resultant regression equation for the quadratic model of the star design was nAbs (%) = 26.142 - 1.044A - 2.065A2 - 0.941B - 0.505B2 + 1.55AB. The second order results of the star design from the variance analysis (ANOVA) showed that the quadratic model is better than the lineal, and gave evidence that, a maximum of 29% absorptiometric color reduction occurs, when an initial pH of 7 and lower K2FeO4 concentration were used. By the same conditions, the reduction of the chemical oxygen demand (COD) was 49.5%. As the reduction of potassium ferrate generate ferric iron salts in aqueous solution, there is a great potential for its combined use as Fe(III) source for Fenton reagent, generating hydroxyl radicals (HO·) by addition of H2O2 to the reaction system. A new design based on RSM was applied, evaluating the potentiality of the oxidationcoagulation-Fenton like process having the pH, Fe(VI) -> Fe(III) and H2O2 as independent variables, and absorptiometric color reduction efficiency as evaluation responses for the dependent variable. The resulting regression equation for the quadratic model was nAbs (%) = 36.9 - 21.58A + 8.37A2 + 1.36B + 0.92B2 + 1.08C + 1.52C2 + 1.27AB - 1.34AC + 1.33BC. The ANOVA results evidenced that the maximum absorptiometric color reduction occurs by pH 3, and by correspondent 10 g L-1 de Fe(VI) and 20 g L-1 hydrogen peroxide. The absorptiometric color and COD reduction were 96% and 57%, respectively. An efficiency increase of the HO· radical generation was achieved when the previous process was combined to UV irradiation, carrying out the so called oxidation-coagulationphoto-Fenton like process. As before, a RSM was applied, where the pH, Fe(VI) -> Fe(III) concentration, H2O2 concentration and temperature were evaluated as independent variables. The efficiency of the absorptiometric color reduction was chosen as dependent variable. The resulting regression equation for the quadratic model was nAbs (%) = 38.3 - 20.2A + 8.12A2 - 0.27B + 3.73B2 + 0.3C + 3.6C2 + 1.67D + 3.1D2 + 1.72AB + 0.51AC - 1.82AD + 0.74BC - 1.11BD + 0.03CD. The ANOVA results evidenced that the maximum absorptiometric color reduction occurs by pH 3 and by 10 g L-1 de Fe(VI) and 20 g L-1 hydrogen peroxide amounts, at 60 °C. The maxima efficiencies achieved for the effluent stream treatment by the oxidationcoagulation-photo-Fenton process were 95% and 85%, for absorptiometric color and COD reduction, respectively. The high efficiency of the combined process as an oxidative-coagulant-oxidative pretreatment for posterior conventional process (e.g., microbiological treatment) can be looked out as an interesting and advantageous alternative for the AW treatment, as well as other recalcitrant streams.